A Micro-RNA Connection in BRafV600E-Mediated Premature Senescence of Human Melanocytes. (24th April 2012) - Ren, Gang; Feng, Jingwei; Datar, Ila; Yeung, Aaron H.; Saladi, Srinivas Vinod; Feng, Yongqing; de la Serna, Ivana; Yeung, Kam C.
Abstract : Recent high-throughput-sequencing of the cancer genome has identified oncogenic mutations in BRaf genetic locus as one of the critical events in melanomagenesis. In normal cells, the activity of BRaf is tightly regulated. Gain-of-function mutations like those identified in melanoma frequently lead to enhanced cell-survival and unrestrained growth. The activating mutation of BRaf will also induce the cells to senesce. However, the mechanism by which the oncogenic BRaf induces the senescent barrier remains poorly defined. microRNAs have regulatory functions toward the expression of genes that are important in carcinogenesis. Here we show that expression of several microRNAs is altered when the oncogenic version of BRaf is introduced in cultured primary melanocytes and these cells undergo premature cellular senescence. These include eight microRNAs whose expression rates are significantly stimulated and three that are repressed. While most of the induced microRNAs have documented negative effects on cell cycle progression, one of the repressed microRNAs has proven oncogenic functions. Ectopic expression of some of these induced microRNAs increased the expression of senescence markers and induced growth arrest and senescence in primary melanocytes. Taken together, our results suggest that the change in microRNA expression rates may play a vital role in senescence induced by the oncogenic BRaf .